PENGARUH BIAYA KUALITAS TERHADAP PENJUALAN PADA PT. GUARDIAN PHARMATAMA - Rilla Gantino; Erwin Erwin (Journal of Applied Finance & Accounting, 2010)
This is an empirical research to determine the influence of the independent variable quality cost to the dependent variable sales. A T-test on prevention cost, valuation cost, internal failure cost, and external failure cost showed significant influence on sales. An F-test on prevention cost, valuation cost, internal failure cost and external failure cost also showed significant influence on sales. Regression analysis was done using the multiple linear regression equation Y = -240710057,3 + 496,753 X1 + 411,237 X2 + 38,384 X3 + 21,283 X4. Regression analysis showed positive that prevention cost, valuation cost, internal failure cost, and external failure cost had a positive influence on sales, which indicates that increasing costs of quality leads to increase in sales. A coefficient determination test (Kd) showed that 95% of quality cost contributes to sales; the remaining 5% is influenced by factors other than cost of quality.